2013
DOI: 10.1063/1.4824392
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and topology determination of complex chemical and biological network systems from first-passage theoretical approach

Abstract: The majority of chemical and biological processes can be viewed as complex networks of states connected by dynamic transitions. It is fundamentally important to determine the structure of these networks in order to fully understand the mechanisms of underlying processes. A new theoretical method of obtaining topologies and dynamic properties of complex networks, which utilizes a first-passage analysis, is developed. Our approach is based on a hypothesis that full temporal distributions of events between two ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 29 publications
4
62
0
Order By: Relevance
“…We have found a universal identity that connects dynamic information, which can be obtained from experimental measurements, with the number of states along the selected path as a first step to unveil the complete structure of the complex network. It is shown that this general result reduces to previously found relations 25,26 for exponential dwell times. Our theoretical predictions are supported by Monte Carlo computer simulations for several networks with different topology.…”
Section: Introductionmentioning
confidence: 40%
See 4 more Smart Citations
“…We have found a universal identity that connects dynamic information, which can be obtained from experimental measurements, with the number of states along the selected path as a first step to unveil the complete structure of the complex network. It is shown that this general result reduces to previously found relations 25,26 for exponential dwell times. Our theoretical predictions are supported by Monte Carlo computer simulations for several networks with different topology.…”
Section: Introductionmentioning
confidence: 40%
“…It suggests that the first-passage time probability function f ij (t) at early times has a power-law dependence (∼t β ), which is similar to results derived in previous studies with exponential waiting times. 25,26 The corresponding exponent β satisfies the equation…”
Section: B the Universal Identity For The Shortest Pathmentioning
confidence: 99%
See 3 more Smart Citations